The Method Of Interpretation Of Syeh Muhammad Abduh And Syeh Rasyid Ridha In The Book Tafsir Al Manar - Zaini, Zaini (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2019)
This article discusses the interpretation motto of Syeh Muhammad Abduh and Syeh Rasyid Ridha whose interpretive pattern has a great influence on the thinking of Islamic reforms in its time and time. By using the comparative method the writer tries to find out the uniqueness of each interpreter both the similarities and the differences.The result can be understood that the two exegetes have interpretive methods and styles which must be different. Al-Manar's interpretation is the greatest work of two figures who are very well known in Muslim intellectuals, he is Syeh Muhammad Abduh as the teacher, and Syeh Rasyid Ridha as a student, in answering various problems with the discourse of contextualizing the interpretation of the verses of the Qur'an ' in the Tafsir Al-Manar Book. Regarding the method he uses in interpretation has many similarities between Syeh Muhammad Abduh and Syeh Rasyid Ridha.